Perancangan produk jam dinding dengan material bonggol jagung - Syarifah Ummu Hany Alatas; Dian Nitta Efafras; Agung Pramudya Wijaya (Institut Seni Indonesia Yogyakarta, 2023)
In general, the materials used in making wall clocks are metal, wood, and plastic. This research utilizes corn cobs as the main material for designing wall clock products that function as timepieces. With, through the design process of this research, a design by drawing approach was carried out which included the stages of analyzing existing industrial data, brainstorming to explore, define and conceptual criteria, as well as designing. Then, all three are formed into a sketch, and ends with making a product prototype. The purpose of this research is to be able to produce wall clock products made from corncobs as an innovation that can improve Indonesian industry, especially in the agro-industrial sector. The expected design result is that the role of this corncob-based wall clock can not only function as a timepiece. However, it can be one of the interior elements that builds good visual quality which in turn can support the atmosphere of the room and provide a novelty value by using corncob material in wall clock products.